Experimental study on calcination and fragmentation characteristics of limestone in fluidized bed. (April 2021) - Miao, Miao; Deng, Boyu; Yao, Xuan; Wei, Guohua; Zhang, Man; Yang, Hairui
Abstract: The fragmentation degree of limestone affects seriously the particle size distribution of sorbent in the desulfurization process in fluidized bed combustion. In this paper, the variation of particle size and differences in microstructure of calcination and fragmentation were measured under different fluidizing medium in the same equipment. The effects of temperature, reaction rate, SO2 and CO2 atmosphere, firing exhaust gas atmosphere on the calcination and fragmentation of limestone with different properties in the fluidized bed were studied. It was found that the size evolution of larger limestone was more obvious than that of finer ones. Under the condition of fragmentation, the particle size evolution of limestone was more intense than that in calcination. The particle size was smaller under the condition of a higher reaction rate. Higher temperature can promote the calcination reaction and reduce the particle size to a certain extent. The coarser fragmentation products at high temperature may be related to the enhancement of agglomeration between particles. SO2 and CO2 can inhibit the fragmentation of limestone and lead to coarsening of products, which further confirms the main contribution of calcination reaction to limestone size evolution. The main chemical reaction in a given atmosphere is direct sulphation reaction and the primary fragmentation is restrained by the high concentration of CO2 in firing exhaust gas, which is more obvious in the oxygen-enriched exhaust gas. Highlights: The size evolution of limestone particles was measured. SEM analysis was used to observe the surface morphology. The effects of temperature and heating rate were studied. The effect of SO2 and CO2 atmosphere was observed. The effect of firing exhaust gas atmosphere was studied.